2021
DOI: 10.1063/5.0050403
|View full text |Cite
|
Sign up to set email alerts
|

On the linear and non-linear fluid response to the circular forcing in a rotating spherical shell

Abstract: Fluid flow excited by a core oscillating in a rotating spherical cavity is experimentally investigated. Oscillations are set by an external inertial field so that in the reference frame of the cavity, the core moves along a circular trajectory around the rotation axis. Two situations are considered: when the core oscillations are co-directed or counter-directed with respect to the rotation of the cavity. The oscillating core is a source of non-axisymmetric inertial waves that form a system of cone-shaped shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…As shown in Fig. 6, but also in Paper I, Tilgner (2007), Morize et al (2010), or Subbotin & Shiryaeva (2021), zonal flows produced by nonlinear self-interaction of non-axisymmetric inertial waves always take the form of nested and axisymmetric cylinders with different angular velocity profiles depending upon cylindrical radius inside the shell. The radial distribution, magnitude and direction of the flow at a given location (prograde or retrograde, i.e.…”
Section: Surface Versus Body Forcingmentioning
confidence: 70%
See 1 more Smart Citation
“…As shown in Fig. 6, but also in Paper I, Tilgner (2007), Morize et al (2010), or Subbotin & Shiryaeva (2021), zonal flows produced by nonlinear self-interaction of non-axisymmetric inertial waves always take the form of nested and axisymmetric cylinders with different angular velocity profiles depending upon cylindrical radius inside the shell. The radial distribution, magnitude and direction of the flow at a given location (prograde or retrograde, i.e.…”
Section: Surface Versus Body Forcingmentioning
confidence: 70%
“…7. The key role of shear layers and critical latitudes in the establishment of these geostrophic flows have already been pointed out for example in the experimental study of Subbotin & Shiryaeva (2021).…”
Section: Surface Versus Body Forcingmentioning
confidence: 88%
“…In a related flow with a cuboid rapidly rotating in an orientation with some walls oblique to the rotation axis and subjected to libration, Wu et al [9] showed that vortex stretching and tilting (inherently 3D nonlinear processes) were most active where the shear layers of the inertial attractor reflect on the wall, leading to the local enhancement of ω 2 well beyond that due to the geometric focusing. Recent experiments in librationally forced spherical shells and cylinders with sloping endwalls have observed similar nonlinear interactions at reflection sites leading to mean shear flows [18][19][20][21][22]. Here, for ω = 0.24, these reflections occur in the equatorial region, and since the mean shears are aligned parallel to the rotation axis, their presence is localized to this region and not readily distinguishable from the focusing shear layers.…”
Section: Primary Viscous Nonlinear Responsesmentioning
confidence: 74%